Resistance to Gender Quotas in Latin America - Gatto, Malu A. C. (Oxford University Press, 2025)
Politicians want to stay in power. Because winners attain office under a given set of electoral rules, any change to these rules is puzzling. When electoral reform does take place, it is expected that changes will better serve those already in power. Perhaps more than any other type of electoral rule, gender quotas are explicit about who is set to win and lose from their adoption. As positive discrimination in favor of women, gender quotas limit the space for men, the clear majority of incumbents. Despite this, gender quotas are now present in every region of the world. But how has this happened? In other words, under what conditions are (men) legislators more likely to support the adoption of gender quotas? Reconstructing three decades of power struggles over quota policymaking in Latin America, the book argues that men legislators are more likely to support gender quotas when opposing the policy also imposes potential costs to their future career prospects—a scenario that has implications for the timing, strength of design, and length of the process of quota policymaking. As the first book to closely trace legislators’ behavior toward gender quotas since the policy made its way into plenary debates, Resistance to Gender Quotas in Latin America employs a wealth of experimental, quantitative, and qualitative data to show how an institution that explicitly seeks to replace incumbents has successfully diffused throughout Latin America despite incumbents’ resistance.